Risk management in the public procurement of innovation: A Conceptualisation - Jakob Edler; Max Rolfstam; Lena Tsipouri; Elvira Uyarra (Public Procurement for Innovation, 2014)
One of the major challenges of public procurement for innovation (PPI) is risk aversion and the limited risk management practices in the public sector (Edler et al., Chapter 2 in this volume). While this problem has been identified for many years (Edler et al., 2005), there have been no attempts to design an effective risk management framework that can be used to alleviate it. The major reason for this is the high level of complexity when it comes to defining, understanding and operationalizing risk, which are necessary in order to make it manageable in the first place. Risks associated with PPI do not only emanate from the nature of the innovation activity itself, but have a large number of different origins associated with the heterogeneity of the actor landscape in PPI. Moreover, different actors have different risk perceptions, and we often find a mismatch between actor groups benefiting from an innovation (users, suppliers, citizens) and those that bear the consequences of its failure. Against this background, the purpose of this chapter is to conceptualize risk and risk management in PPI and discuss the value of such a conceptualization for PPI practice and policy-making. Our conceptualization of risk and risk management in PPI refers to the various types of risks that are relevant to the public procurement process, and indicates some governance and managerial challenges these pose for PPI.